A reverse vaccinology approach identified novel recombinant tick proteins with protective efficacy against Rhipicephalus microplus infestation - Luísa N. Domingues; Kylie G. Bendele; Deanna M. Bodine; Lénaïg Halos; Andre A. Cutolo; Martin Liebstein; Justin Widener; Monica Figueiredo; Yovany Moreno; Christian Epe; Alvimar Jose da Costa; Lucas Vinícius Costa Gomes; et al. (Ticks and Tick-Borne Diseases, 2024)
The cattle tick, Rhipicephalus microplus, causes significant economic losses to the cattle industry. Tick control is predominately achieved via pesticide applications. However, alternative control methods such as vaccines are needed due to the tick's capacity to quickly develop pesticide resistance and to combat tick-borne diseases. We used an in silico reverse vaccinology approach to evaluate and rank open reading frames (ORFs) from the tick's transcriptome for their potential use as anti-R. microplus vaccine antigens. We manually annotated the 200 highest ranked antigens and selected 10 transcript ORFs as vaccine antigen candidates for expression in Pichia pastoris or insect cells. Six of the ten candidate antigens could be successfully expressed and purified in vitro as recombinant proteins with > 1 mg quantity. RT-PCR confirmed the expression of all six transcripts in tick RNA. However, only three of the six transcripts' corresponding ORFs could be confirmed as present in tick tissue protein extracts. Only four of the six vaccine candidate antigens were successfully expressed and purified in sufficient quantity (> 10 mg) for immunogenicity and efficacy trials in cattle. These four were designated BI-TS002, BI-TS004, BI-TS008, and BI-TS009 and sufficient annotation existed that showed sequence similarity to serine‑rich adhesin for platelets, glycine-rich cell wall structural membrane protein, SWM-1 tick serine protease inhibitor, and venom-like dermonecrotic toxins from ticks and spiders, respectively. Cattle immunized with BI-TS004, BI-TS008 and BI-TS009 yielded a statistically significant difference in antibody response post-immunization. This difference was noted on Days 42, 56, 70, and 84 post-immunization for BI-TS008 and BI-TS009, but only on Day 56 for BI-TS004. BI-TS008 and BI-TS009, were formulated with adjuvant and cattle stall tests conducted over a 175 day period to evaluate efficacy against R. microplus infestations. Both an adjuvant only negative control group and a positive control group using the commercially available GAVAC anti-tick vaccine were used. Efficacy was determined by comparing number of engorged adult female ticks, total egg mass weight, and egg hatchability produced from the immunized group to corresponding data from the adjuvant only negative control group. Thus, effects on engorged adult tick number, reproductive capacity, and fertility were measured. Both initial (designated Phase 1 and calculated from tick collections of Days 60–94 days post-first immunization) and long-term (designated Phase 2 and calculated from tick collections of Days 152–175 post-first immunization) efficacies were determined. The overall Phase 1 trial efficacies of BI-TS008, BI-TS009, and GAVAC were 68.3 %, 48.5 %, and 70.7 %, respectively. The overall Phase 2 trial efficacies of BI-TS008, BI-TS009, and GAVAC were 64.4 %, -30.1 %, and 45.1 %, respectively.